Navigating Challenges: An Exploration of Professional Life Skills Application Among Undergraduates in the International Community Service Programmes - Suo Yan ju; Suo Yan Ju, Siti Salmiah Muhammad (IJ-ARPED, 2024)
Professional life skills stand as crucial factors contributing significantly to undergraduates’ academic and employability. Despite their paramount importance, numerous studies have found that undergraduates lack professional skills such as communication and teamwork. This study aimed to identify the challenges in employing professional life skills by undergraduates within the context of international community service programmes in higher education. The qualitative research method was adopted using semi-structured interview questions. The research interviewed four instructors from two different universities who have experience participating in the community service program. The data collected from the interviews were further analysed to answer the research questions. The study found that undergraduates faced many challenges in applying professional life skills to international community service programmes. The study suggested that instructors, universities and policymakers should incorporate life skills into the university curriculum. In addition, Higher education institutions should provide additional training aimed at bolstering skill proficiencies to undergraduates. These proactive steps could bridge the gap and equip undergraduates with the requisite professional life skills essential for success in a globalized world.